Tensile and Flexural Behaviour of Concrete Containing Crumb Rubber as Partial Replacement of Fine Aggregate - Saparuddin, Nurul Ameera (Universiti Teknologi PETRONAS, 2017)
The use of rubber crumb has been introduced in the production of concrete. This alternative is found out to be a great choice in order to significantly reduce the amount of scrap tire disposed in a landfill area. This is because the production of concrete annually could reach up to 500 million tonnes. However, crumb rubber considerably reduced the mechanical strength of concrete, which are compressive, tensile, and flexural strength. Thus, several materials are inserted in the design mix to improve its strength, such as, nano silica, fly ash, and superplastisizer. In this study, firstly, 30 trial mixes of Grade 40 are developed through Respond (RSM) software. Each mix consists of 6 cube samples with the size of 100 x 100 mm. Compressive strength test is done on the samples at 14th day and 28th day. Then, the results are analyzed to come up with the optimum mix design of the rubbercrete. Next, by using the optimum mix design, five mixes of different grade is used for direct tensile test and flexural test. Six samples of each mix design would be produced in the shape of dog-bone and tested for tensile strength of the concrete.